Zinc Nutrition Responses to Agronomic and Yield Traits, Kernel Quality, and Pollen Viability in Rice (Oryza sativa L.) - Kandil, Essam E.; El-Banna, Aly A. A.; Tabl, Dalia M. M.; Mackled, Marwa I.; Ghareeb, Rehab Y.; Al-Huqail, Asma A.; Ali, Hayssam M.; Jebril, Jebril; Abdelsalam, Nader R. (Frontiers in Plant Science, 2022)
Rice (Oryza sativa L.) is one of the major cereal crops worldwide with wheat and maize. Two field experiment were performed to evaluate the response of some rice cultivars to various foliar zinc (Zn) concentrations based on different measurements such as agronomic, yield, yield compounds and grain technological parameters in 2018 and 2019 harvest seasons. The experimental layout was a split plot in three replicates; the five rice cultivars (Skaha 101, Giza178, Yasmeen, Fourate and Amber 33) were distributed in main plots while, the four foliar applications of Zn (1500, 2000, 2500 mg/L beside spray water) were occupied the sub-plots. The finding results showed significant differences among the five rice cultivars regarded to plant height, grain yield, straw yield, biological yield, harvest index, 1000-grain weight, panicle length, protein percentage, and grain Zn content. There is significant effect of Zn on all plant attributes. Significant interaction between rice cultivars and foliar application of Zn was observed, whereas fertilizing Giza 178 with foliar application of Zn at the rate of 2500 mg/L achieved the highest mean values of grain yield and straw yield, biological yield, harvest index, 1000- grain weight, panicle length, protein % and Zn content followed by Sakha 101 with Zn application at the rate of 2000 mg/L, respectively in both seasons. The rice cultivars significantly differed in hulling (%), broken (%), hardness, grain length, shape, amylose (%), gel consistency, and gelatinization temperature. Unfortunately, the commercial Zn product used was genotoxic to pollen grains with the higher rate of Zn . Aberrations were observed such as stickiness, ultrastructural changes in the exterior and interior walls, partially or fully degenerated grains, and shrunken and unfilled grains. This study concluded that using Zn application at the rate of 2000 mg/l to protect human and environmental health, the side effects and toxicity of the local commercial Zn product market should be investigated before making recommendations to farmers.